OP22 Patient-Based Evidence: Its Role In Decision-Making On New Medicines. (2019) - Hems, Sharon; Taylor, Louise; Jones, Jan; Holmes, Eileen
Abstract : Introduction: The Scottish Medicines Consortium (SMC) advises NHS Scotland on the clinical and cost-effectiveness of new medicines. Since 2014, evidence from patients and carers on end-of-life and orphan medicines has been gathered during Patient and Clinician Engagement (PACE) meetings. The output is a consensus statement which describes the added value of a new medicine from the perspective of the patient/carer and clinician. This study investigates the importance of factors identified through PACE to committee members and how these are used in their decision-making. Methods: Survey methodology was used to gain an understanding of the factors from the PACE statement that are most likely to influence members (n = 26) in decision-making. The survey instrument was informed by a literature review and observation of PACE and SMC meetings. Likert scale questions were used to determine the relative importance of factors in the PACE statement, including information relating to eight prominent 'quality of life' themes (family/carer impact, health benefits, tolerability, psychological benefit, hope, normal life, treatment choice and convenience), that were identified by an earlier thematic analysis of these statements. Results: Analysis of survey responses will use mainly descriptive techniques to generate percentages and ranges. Correlation analysis will be considered to investigate relationships between members' demographics, type of medicine (end-of-life, orphan) and the importance of different factors in the PACE statement. Preliminary results indicate that key quality of life themes highly valued by patients/carers are also important to committee members in their decision making. Challenges in assimilating qualitative patient-based evidence from PACE alongside quantitative clinical and economic data were highlighted. Conclusions: Findings from this survey will provide valuable insight into how PACE evidence is used by SMC decision makers alongside traditional clinical and economic evidence and will help shape future improvements to the PACE methodology.